PENYALAHGUNAAN WEWENANG DALAM PENGELOLAAN KEUANGAN DESA (STUDI KASUS PENGELOLAAN APBDES DESA GERBANG SARI KECAMATAN TAPUNG HILIR KABUPATEN KAMPAR TAHUN 2016) - Maulani Novianti; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The issue of village finance is one of the most crucial issues in the implementation of village laws. Corruption is very dominant with administrative law because acts of corruption will only occur in the context of state finances caused by maladministration in the use of authority. The main form of maladministration is abuse of authority. The Village Head of Gerbang Sari has violated Village law number 6 of 2014 that the Village Head is prohibited from harming the public interest, abusing his authority, duties, rights/obligations and committing corruption. This research uses a qualitative approach with a descriptive method that analyzes in detail about certain situations, phenomena and event based on the facts that appear then further analyzed, namely by presenting the results of research on the practices and causes of abuse of authority by village heads in the management of the 2016 APBDes in Gerbang Sari Village, Tapung Hilir District, Kampar Regency.The results of this study, citing the theory of Jean Rivero & Walline, there are 3 forms of abuse of authority, 1) abuse of authority is carried out for personal gain and harm the public interest, 2) abuse of authority that deviates from the purpose of the authority, 3) abuse of authority by abusing procedures. In the practice of abuse of authority by the Village Head of Gerbang Sari if it is associated with the theory of Jean Rivero & Walline according to type number 1, where the abuse of authority is to take actions that are contrary to the public interest and to benefit private interest. Meanwhile, the causes of the abuse of authority in the management of APBDes in Gerbang Sari Village are based on 2 factors. 1)Internal Factors, namely human resource aspects, 2) External Factors, the aspect found are: 1. Regulatory and institutional aspect, 2. Management aspects, 3. Supervision aspects. Keywords: Abuse Of Authority, Maladministration, Village Financial Management.